2012
DOI: 10.1021/nl203597d
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly-Induced Formation of High-Density Silicon Oxide Memristor Nanostructures on Graphene and Metal Electrodes

Abstract: We report on the synthesis of one-dimensional (1D) Li 4 Ti 5 O 12 nanofibers through electrospinning and their outstanding electrochemical performances. Li 4 Ti 5 O 12 with a spinel structure is a promising candidate anode material for lithium rechargeable batteries due to its well-known zerostrain merits. In order to improve the electronic properties of spinel Li 4 Ti 5 O 12 , which are intrinsically poor, we processed the material into a nanofiber type of architecture to shorten the Li + and electron transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
54
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 75 publications
(91 reference statements)
0
54
0
1
Order By: Relevance
“…Silicon-oxide-based resistive random access memory (RRAM) has been widely investigated as a promising candidate of the next-generation nonvolatile memory due to its superior performances and high compatibility with standard CMOS process. [1][2][3][4][5][6][7][8][9][10][11][12] Generally, the SiO x -based RRAM devices can be mainly divided into two categories based on the electrode materials, which are electrochemical metallization memory (ECM) and valence change memory (VCM). For ECM cell, SiO x acts as a solid electrolyte (electron-ion mixed conductor) sandwiched between an electrochemically active metal (i.e., Cu or Ag) electrode and an electrochemically inert metal (i.e., Pt, W, etc.)…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Silicon-oxide-based resistive random access memory (RRAM) has been widely investigated as a promising candidate of the next-generation nonvolatile memory due to its superior performances and high compatibility with standard CMOS process. [1][2][3][4][5][6][7][8][9][10][11][12] Generally, the SiO x -based RRAM devices can be mainly divided into two categories based on the electrode materials, which are electrochemical metallization memory (ECM) and valence change memory (VCM). For ECM cell, SiO x acts as a solid electrolyte (electron-ion mixed conductor) sandwiched between an electrochemically active metal (i.e., Cu or Ag) electrode and an electrochemically inert metal (i.e., Pt, W, etc.)…”
mentioning
confidence: 99%
“…6,7 For VCM cell, SiO x insulator is sandwiched between two inert metal (i.e., Pt, W, TaN) electrodes or metal-free (i.e., polycrystalline Si, carbon nanotube, graphene) electrodes. [8][9][10][11][12][13][14] This type of device shows abnormal unipolar RS (the RESET voltage is larger than SET voltage) with negative differential resistance (NDR) region, which is dominated by the formation/rupture of discrete Si nanocrystal chain inside SiO x matrix due to the electrochemical reaction between SiO x and Si. [8][9][10][11][12][13][14] Similar abnormal unipolar RS phenomenon was also observed in other RRAM systems with embedded nanocrystals, which typically exhibits good uniformity and multilevel storage potential.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these technologies, resistive memory has attracted a great deal of attention because it has simple structure, high-density integration, low-power consumption, and fast operation2345. Previously, Park et al reported an encouraging result that resistive memory can be scaled down to 18 nm6. Recently, other researchers also reported resistive memories in the sub-10 nm scale789.…”
mentioning
confidence: 99%
“…Recently, transition metal oxide based resistive random access memory (ReRAM), as a promising candidate for next generation nonvolatile memory (NVM) application, has been widely studied1112. It shows great characteristics such as fast operation speed, low power, high reliability, multilevel data storage and high density integration131415. More interestingly, some of ReRAM cells show an adaptation response to pulse stimulation, which is quite similar to synapse's behaviors as reported in literature161718.…”
mentioning
confidence: 57%